2022
DOI: 10.3389/fendo.2022.879066
|View full text |Cite
|
Sign up to set email alerts
|

Irisin, Exercise, and COVID-19

Hugo Rodrigues Alves,
Guilherme Schittine Bezerra Lomba,
Cassiano Felippe Gonçalves-de-Albuquerque
et al.

Abstract: Muscle and adipose tissue produce irisin during exercise. Irisin is thermogenic adipomyokine, improves glucose and lipid metabolism, and ameliorates the effects of obesity-driven inflammation, metabolic syndrome, and diabetes. In addition, exercise-induced irisin activates anti-inflammatory pathways and may play an essential role in improving the outcomes of inflammatory conditions, such as coronavirus disease (COVID-19). COVID-19 infection can activate different intracellular receptors and modulate various pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 116 publications
1
22
0
Order By: Relevance
“…The IPA analysis also identified several important signaling pathways involved upon irisin exposure. Interestingly, we found that coronavirus replication pathway was activated upon irisin treatment, though irisin has been reported to counteract the adverse effects of COVID‐19 during the various disease stages, 47 no research up to date has studied its role on coronavirus‐infected hPDL cells yet. The actin cytoskeleton rearrangement is key to both withstanding extracellular mechanical strain and intracellular structural support, and inhibition of actin cytoskeleton leads to down regulation of collagen type I, 48 the activation of actin cytoskeleton signaling may suggest reinforcement of ECM by irisin.…”
Section: Discussionmentioning
confidence: 89%
“…The IPA analysis also identified several important signaling pathways involved upon irisin exposure. Interestingly, we found that coronavirus replication pathway was activated upon irisin treatment, though irisin has been reported to counteract the adverse effects of COVID‐19 during the various disease stages, 47 no research up to date has studied its role on coronavirus‐infected hPDL cells yet. The actin cytoskeleton rearrangement is key to both withstanding extracellular mechanical strain and intracellular structural support, and inhibition of actin cytoskeleton leads to down regulation of collagen type I, 48 the activation of actin cytoskeleton signaling may suggest reinforcement of ECM by irisin.…”
Section: Discussionmentioning
confidence: 89%
“…If one has greater than a high school education, the risk decreases to seven and onehalf percent. Additional risk factors for developing complications of DM consist of tobacco consumption, hypertension, exercise, elevated serum cholesterol, and obesity [6][7][8][9][10][11][12][13]. In regard to obesity, increased body weight leads to impaired glucose tolerance that results in DM progression [14][15][16][17][18][19][20][21][22][23][24].…”
Section: Cellular Metabolism Dysfunctionmentioning
confidence: 99%
“…mTOR can modulate insulin physiology in neurodegenerative studies to increase survival of astrocytes [429], block hyperglycemic endothelial cell injury [430], and preserve metabolic regulation [431]. As a component of the mTOR pathway, the AMP-activated protein kinase (AMPK) modulates cellular metabolism [106,169,198,237,378,381,382,394,432,433], and the activation of AMPK reduces cognitive loss in studies of DM and AD [434,435], removes cerebral Aβ [436] and tau [437], limits Aβ neurotoxicity [392], diminishes long-term inflammation in in the nervous system [10,71,438,439], and fosters pathways for healthy aging [6,440,441].…”
Section: The Mechanistic Target Of Rapamycin and Multiple Sclerosismentioning
confidence: 99%